PENGARUH MODERNISASI SISTEM ADMINISTRASI PERPAJAKAN, SANKSI PAJAK, DAN PELAYANAN FISKUS TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI PADA KPP PRATAMA KUPANG - Lede, Stela Fitriana; Arthana, I Komang; Tameno, Nikson (Universitas Nusa Cendana, 2024)
The aim of this research is to determine the effect of modernization of the tax administration system, tax sanctions and tax services on individual taxpayer compliance at KPP Pratama Kupang partially and simultaneously. The data analysis technique used in this research is a multiple linear analysis technique. The data collection technique was carried out by distributing questionnaires offline and online. The sample used in this research was 100 individual taxpayers registered with KPP Pratama Kupang. The results of this research show that partially, tax sanctions have an effect on individual taxpayer compliance, but the variable modernization of the tax administration system and tax authorities services has no effect on individual taxpayer compliance. Meanwhile, simultaneously the variables of modernization of the tax administration system, tax sanctions and tax service services together influence individual taxpayer compliance.